Government of Mizoram Draft Annual Plan 2009-2010 - Planning Commission (Planning Commission, 2009)
It is regretted that the Draft Annual Plan 2009-10 could not be submitted within the stipulated date due to unavoidable circumstances. In compliance with the Planning Commission’s guidelines and instruction, the Draft Annual Plan 2009-10 has been prepared within a total outlay of Rs. 1100.00 crore which is 10% increase over the current year’s Annual Plan outlay of Rs. 1000.00 crore. Moreover, only 10% increase of Annual Plan outlay is not sufficient to meet even the bare minimum requirement for implementation of developmental works during the Annual Plan 2009-10. Hence, the Government has made a decision that Revised Draft Annual Plan for 2009-10 be prepared afresh by various State Government’s Departments on the basis of their bare minimum requirements which are to be presented and discussed in the Working Group meeting proposed to be held on 18th & 19lh February, 2009. Accordingly, Revised Draft Annual Plan are being prepared by various State Government’s Departments which are to be discussed with their respective counterpart subject Divisions of the Planning Commission.
Planning and Programme Implementation Department Government of Mizoram